A New IoT Application for Dynamic WiFi based Wireless Sensor Network - Ertam, Fatih; Kilincer, Ilhan Firat; Yaman, Orhan; Sengur, Abdulkadir (Institute of Electrical and Electronics Engineers Inc., 2020)
The Internet of Things is the technology that allows the exchange of data between objects through various communication channels. With the development of wireless communication technology, data can be controlled remotely from the devices. Thanks to the dynamic structure of the Internet, the Internet of Things makes an important contribution to the growth of the IT sector and the development of the technology world. In this study, a wireless sensor network based method is recommended for internet of objects. Wireless access devices in the campus networks and ESP8266 devices are connected to each other and a large network of wireless sensors have been developed. Data from the temperature and humidity sensor connected to ESP8266 devices can be monitored via the wireless network in the campus area. The data from the ESP8266 modules used in the study are collected on a server and monitored and reported in real time. It is a significant advantage that the proposed method is a dynamic wireless sensor network and low cost. Considering the advantages that the developed system can be easily used and low cost in existing Wi-Fi networks, it is seen that there is an important study in the literature. © 2020 IEEE.
6th International Conference on Electrical Engineering, ICEE 2020 -- 25 September 2020 through 27 September 2020 -- Virtual, Istanbul -- 164956
Keywords: ESP8266; IoT; Smart systems; WiFi Network; Wireless sensor networks